123-115 Salem Street, ca. 1890 - Unknown (Tufts Archival Research Center, 2005)
Street-level view south-southeast of (left to right) 123-115 Salem Street, located along the east-southeast side of the street. The facades of the buildings face west-northwest. A street light is located on the sidewalk at the corner of Salem and Elmer Streets. Signage adorns the facade of 115 Salem Street and 123 Salem Street, which is visible along the left side of the photograph. A young girl is included in the foreground of the photograph. Other pedestrians are also visible on Salem Street. 5 7/8 x 7 7/8, 7 x 8 7/8 overall Photographs